Fabrication and characterization of lead tin telluride (Pb1-x SnxTe) thermoelectric nanomaterial using horizontal vapor phase growth technique (HVPG) - Sam, Sopheap (Animo Repository, 2018)
Lead Tin Telluride (Pb1-xSnxTe) is known as a promising material in thermoelectric (TE) application because of its rock-salt structure and small energy gap at x = 0.67. Moreover, Horizontal Vapor Phase Growth (HVPG) technique is also known as an effective method to fabricate nanostructure of any material. Therefore, by employing HVPG technique and using Pb1-xSnxTe, the figure of merit of TE material (ZT) was enhanced. HVPG to grow TE material was performed by varying growth temperature from 10000C to 12000C and growth time from 4 hours to 8 hours. According to ANOVA, the interaction term of growth temperature and growth time had a significant effect on response ZT. Using interaction plot in 2k factorial design, at low level of growth time 4 hours, ZT significantly increased as the growth temperature increased from 10000C to 12000C. However, at a high level of growth time of 8 hours, ZT had a small decrease as the growth temperature increased from 10000C to 12000C. Therefore, the value of ZT can be enhanced at 4 hours and 12000C. The highest ZT values about 0.084 and 0.067 were found for sample 3 and sample 4, respectively. Based on Scanning Electron Microscopy (SEM), at high ZT, the nanocubic structure was found. Nanocube is theoretically a rock-slat structure which leads to enhance ZT. The nanowire was captured at high combination growth temperature and growth time. However, based on ANOVA, growth temperature and growth time had no significant effect on the growth of elemental composition namely, Pb, Sn, and Te. Therefore, the variation of ZT in different samples depends on the different nanostructure inside material.